Newcomer to the ACP family - Kasasa, Aya (2001)
Presents an interview with Mr. Rene J. Mujica, the Cuban Ambassador. Looks at Cuba's admittance to the ACP group as the 78th member. Notes that Cuba has become the first ACP country to take no part in cooperation with the European Union under Cotonou.